The impact of metabolic component count on IgA nephropathy prognosis - Hui Ma; Chen Lei; Bo Zhao; Zhihong Feng; Lan Ye; Xuan Wang; Xiaoling Zhou (Scientific Reports)
Abstract Metabolic syndrome, a cluster of conditions including obesity, hyperglycemia, hypertension, and dyslipidemia, is increasingly recognized for its association with kidney disease. However, the impact of metabolic syndrome on the long-term prognosis of IgA nephropathy(IgAN) remains understudied. From August 2009 to December 2018, we conducted a retrospective cohort study at the Department of Nephrology, General Hospital of Ningxia Medical University, involving 698 patients with primary IgAN identified by the initial renal biopsy. Patients were divided into five groups based on the number of metabolic syndrome components they exhibited, including metabolic syndrome with hyperuricemia: Group A (no components), Group B (one component), Group C (two components), Group D (three components), and Group E (four or more components). We compared and analyzed the effect of metabolic components on the prognosis of IgAN. The mean age was 35.83 years, and 51.86% male. The prevalence of metabolic syndrome was 25.07%. The 24-h urine protein quantification correlated positively with metabolic components (P < 0.05), while eGFR correlated negatively (P < 0.05). Kaplan-–Meier analysis showed decreased renal survival with more metabolic components, especially with four or more (P < 0.001). Blood pressure was the most important factor influencing the occurrence of endpoint events in IgAN patients, according to a random forest technique analysis. The incidence of metabolic abnormalities in patients with IgA nephropathy is closely related to the severity of clinical manifestations and poor renal prognosis, with blood pressure being the most critical factor.